Asuransi Usahatani Padi (AUTP) di Subak Gede Penarungan - PURNAMAYANI, NI PUTU ARI; SUSRUSA, KETUT BUDI; PARINING, NYOMAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.2, Desember 2022, 2022)
Rice Farming Insurance (AUTP) at Subak Gede Penarungan The agricultural sector is a sector that has an important role for the Indonesian economy. However, the agricultural sector is currently facing various risks including climate change. Rice Farming Insurance (AUTP) is an alternative systematic risk sharing issued by the government of Indonesia since October 2015. The AUTP program is an implementation of Law no. 19 of 2013 concerning the protection and empowerment of farmers. The decree is followed by the issuance of Minister of Agriculture Regulation Number 40 of 2015 concerning the facilitation of agricultural insurance. Subak Penarungan is one of the subaks in Mengwi District, Badung Regency with the largest proportion of the land areas insured in the regency. This study focuses its analysis on the benefits of rice farming insurance by using quantitative descriptive method, which compares the AUTP claim funds with production costs in one growing season. The responses of farmers on the AUTP program are further analyzed using qualitative descriptive method. This research is expected to contribute to literature in agribusiness, especially on rice farming.